The Role of Social Media Student Language Ethics at Poltekbang Medan : Steps Toward Professionalism, Online Identity, Media Influence, Interpersonal Communication And Compliance - Muhammad Caesar Akbar; Lubis, Anastasia (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
This study investigates the multifaceted influence of social media on the linguistic ethics of students at Poltekbang Medan. It examines how platforms such as Facebook, Instagram, and Twitter shape students' behavior in professionalism, online identity, media influence, interpersonal communication, and adherence to ethical guidelines. Using a mixed-methods approach, data was collected through structured surveys, in-depth interviews, and direct observation involving 109 participants. The findings reveal significant influence of social media on students' linguistic habits, including challenges in maintaining professionalism among peer communication norms. Key recommendations include integrating educational digital literacy and ethical communication training into curriculum to foster responsible online behavior.